The Moderating Role of Corporate Governance on the Relationship between Political Connections and Tax Avoidance - Widarjo, Wahyu; Sudaryono, Eko Arief; Sutopo, Bambang; Syafiqurrahman, Muhammad; Juliati, Juliati (Jurnal Dinamika Akuntansi, 2021)
We analyze the influence of political connections on tax avoidance and the moderating role of corporate governance on the relationship between political connections and tax avoidance. The results of panel data regression analysis on 512 observations of manufacturing companies listed on the Indonesia Stock Exchange from 2014 to 2017 shows that political connections do not have a significant effect on tax avoidance. Furthermore, the results of the moderated regression analysis show that the effectiveness of corporate governance positively moderates the effect of political connections on tax avoidance. Although the results of this analysis indicate that a moderating effect on the effectiveness of corporate governance, but the direction of the regression coefficient is positive. Therefore, the second hypothesis in this study is rejected. The results of this study indicate that the corporate governance mechanism in the sample companies is still not optimal in reducing the level of tax avoidance.